Prediction of spontaneous supratentorial intracerebral hemorrhage acute period outcome on the basis of a complex clinical and neuroimaging investigation and the evaluation of the severity of inflammatory activation in the onset of the disease - A. A. Kuznietsov (Zaporozhye State Medical University, 2018)
The main purpose of the study was to develop multivariate models for the prediction of SSICH acute period on the basis of a complex clinical and neuroimaging study and the evaluation of the severity of inflammatory activation in the onset of the disease. Materials and methods. A prospective, cohort, comparative study was conducted in 203 patients with SSICH (121 men and 82 women, mean age 65.1 ± 0.8 years), who were hospitalized within the first 12 hours since the onset of the disease and received conservative therapy. National Institute of Health Stroke Scale (NIHSS) score, Glasgow Coma Scale score, Full Outline of UnResponsiveness Scale score, intracerebral hemorrhage volume, displacement of the septum pellucidum and pineal gland, white blood cell count (WBCC), neutrophil count, lymphocyte count, monocyte count, neutrophil-to-lymphocyte ratio (NLR) were detected upon admission to the hospital. The functional outcome (FO) of the acute period of the disease was assessed on the 21st day in accordance with the modified Rankin Scale (mRS), whereas >3 points on this scale were considered as an unfavourable FO, ≤3 points were considered as a favourable FO. Binary logistic regression method and ROC-analysis were used for the elaboration of prediction criteria. Results of research. Lethal outcome (12.3 %), unfavourable FO (37.5 %) and favourable FO (51.2 %) were registered in the structure of acute period outcomes of the disease. In accordance with the data of multivariate regression analysis it was determined that admission NIHSS score >16 (Se = 68.0 %, Sp = 93.3 %), septum pellucidum displacement >3 mm (Se = 84.0 %, Sp = 74.2 %) and admission WBCC > 8,600 cells/µL (Se = 84.0 %, Sp = 62.4 %) are independently associated with an increased risk of the lethal outcome of the acute period of SSICH by 12.8 (12.8-26.8) (P < 0.0001), 10.7 (3.8-29.8) (P < 0.0001) and 6.9 (2.4-19.3) (P = 0.0003) times respectively. Admission NIHSS score >9 (Se = 90.5 %, Sp = 66.3 %), septum pellucidum displacement ≥1 mm (Se = 71.6 %, Sp = 71.2 %) and ANLR >2.92 (Se = 86.5 %, Sp = 36.5 %) were independently associated with an increased risk of the unfavourable FO of the acute period of SSICH by 4.9 (2.9-8.3) (P < 0.0001), 2.9 (2.6-3.3) (P < 0.0001) and 2.4 (2.1-2.7) (P < 0.0001) times respectively. Conclusions. Multivariate models for lethal outcome prognosis (AUC = 0.94 (0.89-0.97), Р < 0.01) and unfavourable functional outcome of SSICH prediction (AUC = 0.88 (0.83-0.93), Р < 0.01) were elaborated, which take into consideration the combination of clinical, neuroimaging data and the severity of inflammatory activation in the onset of the disease. Informativeness of elaborated multivariate models, which integrated independent predictors, statistically exceeds informativeness of separate predictors usage in verification of the vital and functional prognosis of SSICH acute period outcome.